Silver–Russell syndrome due to paternal H19/IGF2 hypomethylation in a twin girl born after in vitro fertilization. Issue 10 (16th August 2013) - Cocchi, Guido; Marsico, Concetta; Cosentino, Anita; Spadoni, Chiara; Rocca, Alessandro; De Crescenzo, Agostina; Riccio, Andrea
ABSTRACT Silver–Russell syndrome (SRS) is a clinically and genetically heterogeneous syndrome characterized by severe intrauterine and postnatal growth retardation, facial dysmorphism and body asymmetry. One of the main molecular mechanisms leading to the syndrome involves methylation abnormalities of chromosome 11p15. In the last decades, an increase of imprinting disorders have been reported in children born from assisted reproductive technology (ART); however there is currently little evidence linking SRS and ART. Only few infants with SRS born using ART, supported by molecular analysis, have been described. We report on a twin‐girl conceived using intracytoplasmic sperm injection (ICSI) diagnosed with SRS. Molecular studies revealed a hypomethylation of the paternal H19/IGF2 Imprinting Control Region. Her twin sister had a normal prenatal and postnatal growth and a normal methylation pattern of the chromosome 11p15. This is the second reported case of a twin infant with SRS conceived using ART with hypomethylation of H19/IGF2; it provides additional evidence of a possible relationship between ART procedures and methylation defects observed in SRS. Given the clinical heterogeneity of SRS, and the increased risk of multiple and preterm births in the ART‐conceived children, it is possible that a number of cases of SRS remains undiagnosed in this population. Future studies should investigate the possible link between ART and SRS, in order to better understand the causes of epimutations in ART pregnancies, and to help clinicians to adequately counsel parents who approach to ART and to assess the opportunity of a long‐term follow‐up of children conceived using ART. © 2013 Wiley Periodicals, Inc.